Microbial Consortiums with Promissory Lactic Acid Activity, Isolated from Native Bacterial Inoculants for Silages - Díaz-Monroy, Byron Leoncio; Iglesias, Arabel Elías; Valiño-Cabrera, Elaine (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This work aim was to isolate and characterize strains of LAB, from native microbial preparations (PM), using agroindustrial wastes as whey, bovine manure and rumen contents, designed as biological inoculants for silage processes of post harvest organic waste. Five treatments (microbial preparations, PM + 33% inoculant residue) with 3 replications were evaluated: 1) Treatment control without inoculum (PMSI), 2) Whey (PMSL), 3) Cattle manure (PMEB), 4) Combination of Serum + manure (PMM), 5) Ruminal contents (PMCR). Also were added in all: 20% molasses, 1% urea, mineral salt 1%, and water 45%. They were fermented in plastic containers covered for 96 hours, at 14 °C. hence 3 samples of 500 mL from each PM were obtained and planted in agar MRS (Man, Rogosa and Sharpe), incubated at 37 °C for 72 h under anaerobic conditions (AnaeroGen, Oxoid). LAB strains are catalase and oxidase negative, coco, coco-bacilli and gram-positive non-spore forming. The biochemical identification was performed with the API-50 CHL (BioMérieux, France) system and the database APILAB Plus version 3.3.3. 39 strains LAB were isolated, 4 from PMSI (2 Lactobacillus plantarum, 1 L. brevis, 1 Lactococcus lactis), 12 from PMSL (3 Lactobacillus rhamnosus, 3 L. casei, 2 L. acidophilus and 2 L. paracasei and 2 L. fermentum), 7 from PMEB (3 Streptococcus bovis, 2 Lactobacillus plantarum and 2 Leuconostoc mesenteroides), 10 from PMM (3 Lactobacillus casei, 2 L. plantarum, 2 L. acidophilus, 1 L. fermentum, 1 L. rhamnosus and 1 L. paracasei) and 6 from PMCR (2 Lactobacillus vitulinus, 2 L. ruminus, 1 L. reuteri and 1 Pediococcus damnosus). As conclusion the best source of LAB strains was PMSL, which has the advantage to be a possible bacterial silage inoculant. In all PM were identified homofermentative and heterofermentative LAB strains, associated in microbial consortia. Aditionnally a technological alternative was created to profit from three new agro-industrial wastes.